In vitro activities of ceftazidime/avibactam alone or in combination with antibiotics against multidrugresistant Stenotrophomonas maltophilia isolates - DAMAR ÇELİK, DAMLA (My University, 2023)
Objectives: Infections caused by multidrug-resistant (MDR) Acinetobacter baumannii (A. baumannii) are a growing problem because of the limited options for treatment. The number of antimicrobials that are currently being developed is still insufficient to control this global threat. Combination therapies of antibiotics with different antimicrobial mechanisms have been proposed as the best options for treating MDR A. baumannii infections. The objective of this study was to investigate the in-vitro effectiveness of ceftazidime/avibactam alone or in combination with antibiotics against MDR A. baumannii isolates using time-kill assays. Methods: Forty clinical MDR strains were screened, and minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) of ceftazidime/avibactam, colistin, levofloxacin, meropenem, tigecycline, and tobramycin were determined by microbroth dilution method. The in-vitro synergistic activities of ceftazidime/avibactam with antibiotic combinations were determined by timekill assays at 1 MIC and 4 MIC against five MDR A. baumannii isolates. Results: Based on MIC results, all isolates of A. baumannii were resistant to ceftazidime/avibactam, except for AB-5. All isolates were found to be resistant to meropenem and levofloxacin. At 4 MIC, all of the tested antibiotics showed bactericidal effect (3 log10killing). The synergistic activities of ceftazidime/avibactam + colistin, ceftazidime/avibactam + tobramycin and ceftazidime/avibactam + tigecycline combinations at 1 MIC were observed against studied 5/5, 4/5 and 4/5 strains, respectively. Furthermore, all of the tested combinations at 4 MIC were additive at 24 h. No antagonism was observed. Conclusions: The findings of this study suggest that a significant bactericidal effect was seen with all tested combinations. These findings present significant implications for antibiotic choice for the treatment of infections caused by MDR A. baumannii. © 2018 International Society for Chemotherapy of Infection and Cancer. Published by Elsevier Ltd. All rights reserved.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Farmasötik Mikrobiyoloji; Sağlık Bilimleri; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Pharmaceutical Microbiology; Health Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Clinical Medicine (MED); Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Yaşam Bilimleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Life Sciences; Ceftazidime/avibactam; Combination; β-Lactam inhibitors; Gram-negative; Synergy